Research on the fairness of QoS degradation in multimedia wireless networks - ZHANG Xue (Tongxin xuebao)
The fairness of QoS degradation of multi-class and multi-priority adaptive multimedia applications in wireless/mobile multimedia networks was studied.A degradation principle minimizing the weighted sum of degradation factor’s square（MWSDFS） was proposed,considering not only inter-class and intra-class priority but also user’s QoS degradation degree.Then,the degradation principle of MWSDFS is proved satisfying the generalized proportional fairness for discrete multimedia applications,and proportional fairness for continuous adaptive multimedia applications.At last,quantum genetic algorithm is used to solve the given problem,and the results further validate the effectiveness of the proposed algorithm.